2015
DOI: 10.1016/j.nano.2015.06.003
|View full text |Cite
|
Sign up to set email alerts
|

Movement of magnetic nanoparticles in brain tissue: mechanisms and impact on normal neuronal function

Abstract: Magnetic nanoparticles (MNPs) have been used as effective vehicles for targeted delivery of theranostic agents in the brain. The advantage of magnetic targeting lies in the ability to control the concentration and distribution of therapy to a desired target region using external driving magnets. In this work, we investigated the behavior and safety of MNP motion in brain tissue. We found that MNPs move and, form nanoparticle chains in the presence of a uniform magnetic field, and that this chaining is influenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
31
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 53 publications
(31 citation statements)
references
References 54 publications
0
31
0
Order By: Relevance
“…Detected MNPSNP clusters in the brain might be sporadically located inside larger blood vessels [66,67]. It is assumed that they did not cross the blood brain barrier and were transported via blood flow to other organs being trapped there [68][69][70]. In addition, MNPSNPs were not supposed to cause any damage in the brain Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Detected MNPSNP clusters in the brain might be sporadically located inside larger blood vessels [66,67]. It is assumed that they did not cross the blood brain barrier and were transported via blood flow to other organs being trapped there [68][69][70]. In addition, MNPSNPs were not supposed to cause any damage in the brain Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Determination of Cellular Uptake by TEM : To investigate the internalization and cytocompatibility, HepG2 cells were incubated with the nontargeted (MMSN‐S 2 ‐PEI‐PEG), single‐targeted (MMSN‐S 2 ‐PEI‐PEG‐PBA M−), and dual‐targeted (MMSN‐S 2 ‐PEI‐PEG‐PBA M+) formulations, during which a 0.3 T Nd‐Fe‐B button magnet was fixed beneath the plate of the dual‐targeted MMSN. After incubation at 37 °C for 6 h, cells were washed with PBS in triplicate, detached by 0.25% trypsin, and the cell suspension was centrifuged (2000 r min −1 , 10 min).…”
Section: Methodsmentioning
confidence: 99%
“…The body weight and tumor volume were monitored every 2 d. Tumors were dissected and measured to evaluate the therapeutic efficacy on 10th and 21st day, respectively. The inhibition rate (%) at 21st day was determined as ( C − T )/ C × 100%, where C was the tumor weight of the control group, and T was the tumor weight of each treated group …”
Section: Methodsmentioning
confidence: 99%
“…Note that particles are often treated by the FDA as drugs, although in Europe, they may be treated as devices. Studies of ex vivo vital rodent brain slices have shown that the presence of magnetic particles does not cause a measurable disruption of function [17]. In fact, it is not unusual for humans living in industrial cities to have magnetic particles in their brains, with no known related diseases [18].…”
Section: Particle Toxicitymentioning
confidence: 99%